1993
DOI: 10.1016/0020-7292(93)90270-7
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pregnancy in diabetic mothers

Abstract: Fetal and neonatal risks associated with diabetes in pregnancy depend not only on the severity, but also on the type of diabetes. In modern societies fetal complications associated with diabetes are mainly those due to hyperglycemia in the second half of gestation. The results also emphasize the fact that perinatal morbidity rather than mortality should be the yardstick for the efficacy of management of diabetes in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
1
9
0
2
Order By: Relevance
“…The high rate of hypoglycaemia in our IDMs is similar to findings by other authors [13,14,18] and has been identified as a marker of poor glycaemic control in the mother. A rapid decline in plasma glucose concentration is characteristic of the IDM, especially one whose mother's diabetes is poorly controlled [10,13].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The high rate of hypoglycaemia in our IDMs is similar to findings by other authors [13,14,18] and has been identified as a marker of poor glycaemic control in the mother. A rapid decline in plasma glucose concentration is characteristic of the IDM, especially one whose mother's diabetes is poorly controlled [10,13].…”
Section: Discussionsupporting
confidence: 91%
“…The study also showed a low mortality rate among IDMs, although still higher than in the non- IDMs. Although perinatal mortality among this group has declined [10,11], neonatal morbidity remains a significant challenge [12-14]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although perinatal mortality among this group has declined, 1,2 excess neonatal morbidity remains a significant challenge. [3][4][5] Suboptimal prenatal care along with poor maternal glycemic control, vasculopathy, infection, and pregnancy-induced hypertension are factors associated with poor perinatal outcome. 1,6,7 Congenital malformations, [8][9][10] macrosomia, 3,11,12 respiratory distress syndrome (RDS), 13,14 hypoglycemia, 3,[15][16][17] hyperbilirubinemia 18 and hypocalcemia 19 are some of the conditions most frequently diagnosed in the offspring of diabetic women.…”
mentioning
confidence: 99%
“…Several studies have reported hypocalcemia in babies born to diabetic mothers. [2526] Tsang et al . advanced the hypothesis that hyperparathyroidism of diabetic mothers might suppress the fetal parathyroid function and lead to hypocalcemia of the newborn.…”
Section: Discussionmentioning
confidence: 99%